Interhemispheric Activation and Memory Function: Considerations and Recommendations in the Context of Cardiovascular Exercise Research. Issue 6 (December 2019) - Loprinzi, Paul D.; Frith, Emily
The field of neurobiology of learning and memory has demonstrated that interhemispheric activation plays an important role in subserving episodic memory function. A common behavioral technique to induce interhemispheric activation includes saccadic eye movements, with a common behavioral marker being the degree of handedness. Importantly, however, the field of exercise neurobiology has yet to consider these behavioral techniques and markers in exercise-based studies. This review highlights the effects of these techniques and markers on episodic memory function and discusses the implications of this for exercise studies. We discuss the physiological and neurological mechanisms of interhemispheric activation on memory. We also discuss the role this may play in cardiorespiratory exercise studies. Our understanding of the role of both exercise and interhemispheric activation on memory function is improving. The interplay between these two factors on memory, however, is unknown. We discuss these implications and provide recommendations for future research.